2018
DOI: 10.1007/s10695-018-0492-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of fermented and non-fermented de-oiled rice bran with or without exogenous enzymes supplementation in the diet of Labeo rohita (Hamilton, 1822)

Abstract: A 60-day feeding trial was conducted to study the effect of exogenous enzymes (xylanase and phytase) supplementation in the non-fermented and fermented de-oiled rice bran (DORB)-based diet of Labeo rohita. Four test diets (T1-DORB-based diet, T2-fermented DORB-based diet, T3-phytase and xylanase supplemented DORB-based diet, and T4-phytase and xylanase supplemented fermented DORB-based diet) were formulated and fed to the respective groups. Test diets T3 and T4 were supplemented with 0.01% xylanase (16,000 U k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…The findings of Kumar et al (2017), Kumar Sahu, and Ranjan (2018), Kumar, Sahu, Shamna, et al (2018), Lovell (1989)), Meshram et al. (2018), Ranjan, Sahu, Deo, Kumar, Kumar, et al (2018), Ranjan et al (2018) and Anand et al (2020) also reported the similar findings. GSI and HSI showed no significant difference ( p > 0.05) between different experimental groups.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The findings of Kumar et al (2017), Kumar Sahu, and Ranjan (2018), Kumar, Sahu, Shamna, et al (2018), Lovell (1989)), Meshram et al. (2018), Ranjan, Sahu, Deo, Kumar, Kumar, et al (2018), Ranjan et al (2018) and Anand et al (2020) also reported the similar findings. GSI and HSI showed no significant difference ( p > 0.05) between different experimental groups.…”
Section: Discussionmentioning
confidence: 52%
“…Nutrient digestibility is positively correlated with the digestive enzyme activity of any species (De et al., 2015). Digestive enzyme influences the digestive process and improves the growth performance of animals (Anand et al, 2020; Kumar et al, 2019, 2017; Kumar, Sahu, & Ranjan, 2018; Kumar, Sahu, Shamna, et al, 2018; Lemieux et al., 1999; Meshram et al., 2018; Ranjan, Sahu, Deo, Kumar, Kumar, et al, 2018; Ranjan et al, 2018). The ability of any fish to digest and absorb nutrients depends on the presence of anti‐nutrients, dietary fibre content and the quality of digestive enzymes (Anand et al, 2020; Meshram et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labeo rohita is a commercially important freshwater fish, which is widely cultured in Asia and in Indian subcontinent (Iqbal et al, ; Ranjan et al, ; Ranjan, Sahu, Deo, Kumar, Kumar, et al, ; Ranjan, Sahu, Deo, & Kumar, ). Semi‐intensive carp culture system is predominant in the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, fish farmers are emphasizing to use the cheaper ingredients for feeding the fish. As a present practice, DORB is the major and most commonly used feed ingredient for carp feeds in the country and is used by carp farmers either singly or in combination with other ingredients (Kumar, Sahu, Shamna, & Ranjan, ; Kumar, Sandor, et al, ; Ramakrishna, Shipton, & Hasan, ; Ranjan, Sahu, Deo, Kumar, Kumar, et al, ; Ranjan, Sahu, Deo, & Kumar, ). After DORB, farmers prefer to use GNOC and CSOC in the carp feed.…”
Section: Introductionmentioning
confidence: 99%